Nudging Urban Food Pantry Users in Utah Toward Healthier Choices. Issue 5 (September 2021) - Coombs, Casey; Savoie-Roskos, Mateja R.; LeBlanc, Heidi; Gast, Julie; Hendrickson, Jackie
Purpose. To evaluate the impact of a nudge program on food pantry clients' self-reported selection and use of healthy foods. Method. A convenience sample of clients of six urban food pantries in Utah were surveyed about their experience with the Thumbs Up for Healthy Choices nudge program. Chi-square tests were used to identify associations between demographic characteristics and self-reported program impact. Results. Ninety-four percent (n = 158) of respondents agreed that the program made it easier to make healthy choices. Sixty-five percent reported healthier diets since its implementation. Additionally, Hispanic respondents were more likely to report positive impacts than non-Hispanic respondents. Conclusions and Implications. Nudge programs are effective in increasing the selection of healthy foods among pantry clients in Utah. Impacts seemed to be particularly positive for Hispanic pantry users in Utah. Nutrition programs should consider implementing these low-cost strategies to improve dietary quality of pantry users.